Loss-of-function mutations in ATP6AP1 and ATP6AP2 in granular cell tumors - Fresia Pareja (Nature Portfolio, 2018)
Granular cell tumors (GCTs) are rare tumors that arise in multiple anatomical locations. Here, the authors investigate the genomics of GCTs, finding inactivating somatic mutations in ATP6AP1 or ATP6AP2 in 72% of the 82 GCTs analyzed. In vitro manipulation of these genes recapitulated GCT phenotypes in cellular models.